Rukavisсhnikovia, a new replacement name for preoccupied Iliella Rukavishnikova, 1980 (Brachiopoda) non Tschernyshev, 1940 (Crustacea) - Doweld, Alexander B. (Zootaxa, 2015)
The generic name Iliella was proposed by Rukavischnikova (Nikitin & al., 1980: 71; type species I. minima Rukavischnikova, by original designation) for a new fossil brachiopod genus from the Upper Ordovician (Katian: Chokparian horizon) of the north of Dulankara mountains (Southern Kazakhstan, Central Asia). However, this name is already preoccupied by a fossil branchiopod generic name Iliella Tschernyschev (1940: 12, 32), which is in current use (Crustacea: Branchiopoda: Ketmeniidae Novozhilov, 1957), described from the Lower Jurassic deposits of Ketmen’ mountains of Central Asia.